Do NSAIDs Take Us Away From Treatment Goals in Axial Spondyloarthritis: A Story About Dysbiosis or Just a Matter of Bias? - Queiro-Silva, Rubén; García-Valle, Andrea; Alonso-Castro, Sara; Alperi-López, Mercedes (Frontiers in Medicine, 2021)
Non-steroidal anti-inflammatory drugs (NSAIDs) remain the mainstay of treatment for spondyloarthritides (SpA), a group of entities with common clinical and pathophysiological aspects, but also with differential features. Although NSAIDs provide significant symptomatic relief, especially for joint pain and morning stiffness, their role in achieving and maintaining the treatment goals advocated by the treat to target strategy in SpA is not entirely clear. These agents can induce changes in the composition of the intestinal microbiota, also favoring an alteration of the barrier function in the gut epithelium. All of this, favored by a pre-disposing genetic background, could activate a specific type of aberrant immune response in the gut lamina propria, also known as type-3 immunity. This article offers a perspective on how NSAIDs, despite their undeniable value in the short-term SpA treatment, could hinder the achievement of medium and long-term treatment goals by compromising the barrier function of the gut mucosa and potentially altering the composition of the gut microbiota.